2015
DOI: 10.1002/acr.22577
|View full text |Cite
|
Sign up to set email alerts
|

Role of Sleep Disturbance, Depression, Obesity, and Physical Inactivity in Fatigue in Rheumatoid Arthritis

Abstract: Background/Purpose: Fatigue is a major concern for individuals with rheumatoid arthritis (RA). However, in order to treat fatigue adequately, its sources need to be identified. Methods: Data were collected during a single home visit (n=158). All participants had physician-diagnosed RA. Assessments were made of self-reported sleep quality, depression, physical activity, RA disease activity, muscle strength, functional limitations, and body composition. Information was collected on demographics, medications, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
73
1
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 68 publications
5
73
1
5
Order By: Relevance
“…Our study suggests that fatigue is not well represented in physician‐based evaluations, such as the DAS28 or MDGA, but is an important component of a patient's self‐perceived well‐being as indicated by its correlation with PGA scores. A recent study found that the fatigue experienced by patients with RA is associated with RA disease activity, poor sleep quality, depression, and obesity 25; accordingly, improvements in disease activity alone may not be sufficient to decrease a patient's overall fatigue. Of the 3 PROs we evaluated, fatigue was the least likely to improve.…”
Section: Discussionmentioning
confidence: 99%
“…Our study suggests that fatigue is not well represented in physician‐based evaluations, such as the DAS28 or MDGA, but is an important component of a patient's self‐perceived well‐being as indicated by its correlation with PGA scores. A recent study found that the fatigue experienced by patients with RA is associated with RA disease activity, poor sleep quality, depression, and obesity 25; accordingly, improvements in disease activity alone may not be sufficient to decrease a patient's overall fatigue. Of the 3 PROs we evaluated, fatigue was the least likely to improve.…”
Section: Discussionmentioning
confidence: 99%
“…RA predisposes individuals to many of the factors that comprise the Fried definition of frailty, including sarcopenia, fatigue, and low activity [711]. However, the prevalence of frailty among individuals with RA has not been examined.…”
Section: Introductionmentioning
confidence: 99%
“…Physical inactivity has been significantly associated with RA fatigue, and its effects appear to be mediated by a range of non-RA-specific variables that are important predictors of fatigue, for example, poor sleep quality, depressive symptoms and obesity 13 .…”
Section: How the Intervention Might Workmentioning
confidence: 99%
“…Regular participation in PA might reduce the impact of RA fatigue by moderating these associated risk factors 13 .…”
Section: How the Intervention Might Workmentioning
confidence: 99%
See 1 more Smart Citation